Dampak Undang-undang Omnibus Law terhadap Perdagangan Internasional Non-Migas di Indonesia - Mohammad Wahed; Muhammad Roby Setiawan (University Merdeka Malang, 2022)
This study aims to determine whether there is a difference between the value of non-oil and gas exports and imports before and before the enactment of the Omnibus Law in Indonesia in November 2020 - October 2021. The data used is secondary data in the form of non-oil and gas exports and imports from 2019 to 2021. sourced from BPS (Central Statistics Agency). The method used is quantitative, and data analysis uses paired sample t test. The results of the study show that the average value of non-oil and gas exports and imports before the enactment of the Omnibus Law is greater than before. This means that there was an increase in non-oil and gas exports prior to the enactment of the Omnibus Law. The results also show that the significance obtained for non-oil and gas exports is 0.000, which is smaller than 0.05, so Ho is rejected and Hi is accepted. It can be said that there were differences in non-oil and gas exports prior to the enactment of the Omnibus Law (EX1) and before the enactment of the Omnibus Law (EX2). Meanwhile, non-oil and gas imports obtained a significance value of 0.001 which means the significance is less than 0.05, then Ho is rejected and Hi is accepted. Thus, there is a difference between non-oil and gas imports prior to the enactment of the Omnibus Law (IM1) and before the enactment of the Omnibus Law (IM2).